IDENTIFIKASI KARAKTERISTIK SPATIAL QUESTIONS MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR PADA MATERI GEOMETRI - Indah Setyo Wardhani (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
This research aims to identify the characteristics of spatial questions of PGSD students based on a taxonomy of spatial thinking. This type of research is descriptive research with subjects as many as 22 students selected from 120 PGSD students at Trunojoyo University based on certain criteria. The results of the research were 560 spatial questions which were created by research subjects after being given 6 spatial image objects. The characteristics of the 560 spatial questions based on the taxonomy of spatial thinking are: 414 (73,93%) at primitive spatial level, 99 (17,68%) at simple spatial level, 22 (3,92%) at complex spatial level, 10 (1,79%) non-spatial level. These results conclude that the spatial questions characteristics of the subject tend to be at the primitive spatial level which leads to lower cognitive questions. Other research findings included 15 (2,68%) spatial questions that were not accommodated in the taxonomy of spatial thinking, giving rise to indications of the addition of a new level.